Context and contextuality : the mission of migrant churches with a focus on the Pacific Coast Slavic Baptist Association /. - Tsvirinko, Vyacheslav (Carlisle, Cumbria, UK : Langham Monographs, 2018)
Since 1988, hundreds of thousands of Evangelical Christians have migrated to the United States of America from former Soviet Union countries, establishing many Russian-speaking immigrant congregations across the country. This study analyzes how these immigrant churches function in their new cultural, social, and religious context. Dr Vyacheslav Tsvirinko, a Russian who lived in the USA for over twenty-five years, examines the holism, authenticity and contextuality of the mission work done by churches in the Pacific Coast Slavic Baptist Association (PCSBA) in America. He defines authentic mission in light of three major Christian groups - the World Council of Churches, the Lausanne Movement, and Anabaptists - and uncovers startling insights on how PCSBA churches engage in mission, both back in their homeland and in the USA. The findings and conclusions of this work are invaluable to diasporic Christian communities who wish to address their authenticity in the way they do mission, both internationally and in their local context, creating a path to more fruitful gospel and kingdom work."--Publisher.
Includes bibliographical references.
Keywords: Pacific Coast Slavic Baptist Association; Emigration and immigration -- Religious aspects -- Christianity; Russian Americans -- Religious life; Church work with immigrants; Church work with immigrants; -- Russian Americans -- Religious life